Hubungan Iklim Dengan Kejadian Penyakit Leptospirosis Di Indonesia: Literatur Review - Muhammad Mirza Ramadhan; Sri Devi; Tirana Cahya Mahrani Ismail; Zaitun Mulyani; Ramadhan Tosepu (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
Leptospirosis is a direct zoonosis where transmission occurs directly, without the use of other vectors, and humans are accidental hosts that are unintentionally related to infective animals or Leptospira contaminated material. Leptospirosis is a public health problem throughout the world, especially tropical and subtropical countries that have high rainfall, and is also a major problem in temperate regions. Leptospirosis is zoonosis due to Leptospira bacteria. Leptospirosis is a whole world with a broad spectrum of animals as its host. Infection that occurs in humans that occurs, after contact with air or other materials contaminated with animal waste. The aim is to study the relationship with the incidence of leptospirosis. The method used in this article is a literature review. Library sources used in preparation of literature review use journal articles from 2015 to 2017, the process of searching through Google Scholar articles. Journal discussion results show air temperature, humidity, increase in rainfall, air pH, and flood events have an influence on leptospirosis. Relationship between events with leptospirosis. The conclusion in this journal explains that there is a relationship between complications and the incidence of leptospirosis.